The Problem of Teaching and Learning Calculus in Engineering - García Retana, José Ángel (2013)
Teaching and learning Mathematics, and specifically Calculus, represents one of the major difficulties for college students, including engineering students. So far, the methods used to face such difficulties have not been successful; reducing the basic algebra to arithmetic and algorithmic processes has led to a process of de-contextualization of that discipline. Thus, calculus educators need to reflect on the characteristics of engineering in order to make calculus an educational instrument for engineering education.